Beyond prime time activism communication activism and social change - Ryan, Charlotte 1949-; Jeffreys, Karen 1960- (New York London Routledge,Taylor & Francis Group, 2019)
In this accessible introduction to communication activism, organizer Karen Jeffreys and sociologist Charlotte Ryan draw on more than two decades of ongoing collaboration, using the Rhode Island Coalition for the Homeless (RICH) as a case study. The book examines a community with shared values, decision-making, and conflict resolution procedures, tracking its organizing strategy and matched communication plan. The authors first describe a communication campaign during the welfare reform battles (1990-1995) in which they began to practice communication activism. In ongoing work with two organizations over the next two decades, they distil a model of communication activism that draws directly from vibrant traditions of empowerment communication in U.S. social movements and movements from the Global South. Beyond Prime Time Activism provides students and researchers with an invaluable look at contemporary activism practices and with practical tools tried and tested in two decades of social movement engagement. This book is ideal for anyone participating in social change movements or studying how they navigate communication and media inequalities.
Models -- Why it takes a whole social movement to raise an issue -- Public communication models -- Communication activism for social change -- Practices -- Learning communities as movement safe spaces -- From organizing strategy to communication strategy -- Framing stories -- Sustaining communication activism -- Continuous inquiry : learning from experience -- Learning through research collaborations -- Sustaining communication activism : lessons & unresolved challenges -- Appendix -- Strategic communication practices -- Communication assessment tool -- Strategic communication planning worksheet -- Message development worksheet.
Prof. Belinda Espiritu (Recommending faculty) - Bookfair 2019
Includes bibliographical references and index.
Keywords: Social movements; Public relations and politics; Mass media -- Political aspects; Social change